MiR-126 in intestinal-type sinonasal adenocarcinomas: exosomal transfer of MiR-126 promotes anti-tumour responses - Tomasetti, Marco; Re, Massimo; Monaco, Federica; Gaetani, Simona; Rubini, Corrado; Bertini, Andrea; Pasquini, Ernesto; Bersaglieri, Cristiana; Bracci, Massimo; Staffolani, Sara; Colomba, Mariastella; Gregorini, Armando; et al. (BMC cancer, 2018)
BACKGROUND: Intestinal-type sinonasal adenocarcinomas (ITACs) are aggressive malignancies related to wood dust and leather exposure. ITACs are generally associated with advanced stage at presentation due to the insidious growth pattern and non-specific symptoms. Therefore, biomarkers that can detect the switch from the benign disease to malignancy are needed. Essential for tumour growth, angiogenesis is an important step in tumour development and progression. This process is strictly regulated, and MiR-126 considered its master modulator. METHODS: We have investigated MiR-126 levels in ITACs and compared them to benign sinonasal lesions, such as sinonasal-inverted papillomas (SIPs) and inflammatory polyps (NIPs). The tumour-suppressive functions of MiR-126 were also evaluated. RESULTS: We found that MiR-126 can significantly distinguish malignancy from benign nasal forms. The low levels of MiR-126 in ITACs point to its role in tumour progression. In this context, restoration of MiR-126 induced metabolic changes, and inhibited cell growth and the tumorigenic potential of MNSC cells. CONCLUSIONS: We report that MiR-126 delivered via exosomes from endothelial cells promotes anti-tumour responses. This paracrine transfer of MiRs may represent a new approach towards MiR-based therapy.
Keywords: senioři; nádory nosu; Biomarker; Keratin-20; exozómy; MiR-based therapy; Wood; MiR-126; regulace genové exprese u nádorů; mikro RNA; nádory vedlejších dutin nosních; Middle Aged; Inflammatory polyps; mužské pohlaví; adenokarcinom; Cell Proliferation; Adult; MicroRNAs; Biomarkers, Tumor; Intestinal-type sinonasal adenocarcinomas; ženské pohlaví; nádorové biomarkery; Humans; Gene Expression Regulation, Neoplastic; keratin-20; Sinonasal-inverted papillomas; Paranasal Sinus Neoplasms; patologická angiogeneze; Exosomes; dřevo; lidé středního věku; Neovascularization, Pathologic; proliferace buněk; dospělí; Female; Aged; Nose Neoplasms; Adenocarcinoma; lidé; Male